Behavioural Determinants of Smart Home Device Adoption: An Empirical Study in Jeddah, Saudi Arabia - Dr. Tawfik AlNahdi; Dr. Chouayb Larabi; Dr. Farrukh Nawaz Kayani (Decision Making: Applications in Management and Engineering, 2025)
The smart home gadget industry is expanding quickly on a global scale, yet little is known about the purchasing habits of consumers in these areas. The current study uses the Theory of Planned Behaviour to investigate the behavioural intention of consumers in Jeddah, Saudi Arabia, who plan to buy smart home appliances. It examines the effects of attitude, perceived behavioural control, and subjective norm on purchase intentions in greater detail. Of the 450 respondents that received surveys, 388 were used for analysis after the questionnaires were delivered. Self-administered questionnaires were used in a quantitative cross-sectional survey design as part of the methodology. The associations between important variables were investigated using regression analysis, and the constructs were validated using factor analysis. The findings show that purchase intentions are significantly positively correlated with both subjective norms and perceived behavioural control, with perceived behavioural control being the most important predictor. However, attitude did not seem to be a major factor, indicating that in this situation, practical needs and social influence are more important than personal preferences. These results highlight how crucial it is to use social influence and build customer trust through focused marketing strategies, such as educational campaigns and affordable prices, in order to promote the uptake of smart home technology. For scholars, marketers, and legislators interested in advancing smart technology in Saudi Arabia and other developing countries, this study offers insightful information.